Analisis Sistem Proteksi Rele Differensial Pada Busbar Di Gardu Induk 150 kV Paokmotong - rosihan adi wijaya; supriyatna; sultan (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2025)
Substations are an important component in the transmission and distribution system of electric power. This substation functions as a point of distributing electricity from the plant to the end consumer by changing the voltage level for power delivery efficiency. The critical element in the substation is the busbar or bus, which serves as a link between electrical equipment such as transformers, circuit breakers, and transmission lines. Busbars at the Substation play an important role in maintaining the continuity and stability of the electric power system. Busbars are also vulnerable to disturbances, such as short circuits that can cause major damage and widespread disruption of electrical services. Fast, sensitive, and reliable protection systems are needed to detect and isolate disturbances in the busbar to prevent more severe damage and ensure the safety and stability of the electric power system. An effective method of protection for busbars is to use differential relays. Differential relays work on the principle of ratio of inlet and outflow currents out of the protection zone. Data processing in the form of calculation of differential relay setting in the form of calculation: finding the value of the CT ratio, secondary current in the CT, differential current, strain current, slope percent and setting current. The next stage is to simulate the differential relay working system through ETAP 19.0.1 software. The differential current value (Id) is 0.924 A and the restrain current (Ir) is 1.012 A, slope1 is 91.24% and slope2 is 182.48%, and the differential relay setting current value is 1.2012 A. The differential relay performance in the ETAP simulation is 100% working well. When there is a 3-phase internal symmetrical disturbance of 2.708 A, the differential relay works, and when there is an external symmetrical 3-phase disturbance , 1.486 A causes the differential relay not to work.